2000
DOI: 10.1074/jbc.275.11.8161
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dual Repressor Elements for Neuronal Cell-specific Transcription of the Rat 5-HT1A Receptor Gene

Abstract: The serotonergic neurons of the raphe nuclei are the primary site of serotonin synthesis in the brain. They send projections to a wide variety of brain regions, including the hippocampus, cortex, limbic system, and hypothalamus (1). Activation of postsynaptic receptors in the above regions is associated with serotonergic regulation of memory, motivation, emotion, neuroendocrine stress response, etc. (2-4). The activity of serotonergic neurons of the raphe nuclei is regulated in part by presynaptic autoreceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
114
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 66 publications
(122 citation statements)
references
References 32 publications
5
114
0
3
Order By: Relevance
“…The 5-HT1A receptor gene is regulated by a proximal promoter and an upstream repressor region that determines basal expression in neuronal cells (14,15). In the human 5-HT1A repressor region, we previously identified a functional C(Ϫ1019)G polymorphism associated with major depression and suicide, as well as anxiety-related phenotypes, which has been replicated in independent studies (16,17).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The 5-HT1A receptor gene is regulated by a proximal promoter and an upstream repressor region that determines basal expression in neuronal cells (14,15). In the human 5-HT1A repressor region, we previously identified a functional C(Ϫ1019)G polymorphism associated with major depression and suicide, as well as anxiety-related phenotypes, which has been replicated in independent studies (16,17).…”
mentioning
confidence: 82%
“…Briefly, sense and antisense oligonucleotides of the human (26C) and mouse (mouse#1, 5Ј-GGAGAGTCTCTGAGGGTTTTCCTCGTGC-CTGATA) Deaf-1 elements synthesized with GG 5Ј-overhangs were hybridized and labeled with [ 32 P]dCTP using Klenow fragment DNA polymerase (15). Purified bacterially expressed human Deaf-1 protein (5 or 7.5 g/reaction) was preincubated with or without competitor DNA in a 20-l reaction containing labeled probe in DNA-binding buffer (20 mM HEPES, 0.2 mM EDTA, 0.2 mM EGTA, 100 mM KCl, 5% glycerol, and 2 mM DTT, pH 7.9), 1 g of poly(dI-dC), at 22°C for 20 min and resolved on a nondenaturing 5% acrylamide/Tris-glycine gel at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of transfected Chinese hamster ovary cells with 5-HT 1A agonists has been shown previously to increase 5-HT 1A receptor density via activation of the NF-B pathway, by stimulating the degradation of the inhibitory subunit, I-B (32). Two consensus NF-B binding sites (at Ϫ64 and Ϫ365 bp upstream from the initiation ATG) are located in a region with strong enhancer activity that is highly conserved in rat and mouse (33)(34)(35). In addition, recent studies have shown that the p50/p65 subunits of NF-B are positive regulators of the rat 5-HT 1A receptor promoter activity (36).…”
Section: -Ht 1a Receptor Protein Expression In Splenocytes Andmentioning
confidence: 99%
“…These include the RE-1 site for neural restrictive factor (REST/NRSF) [76] and a powerful dual repressor element that is regulated by a pair of conserved repressors, Freud-1/ CC2D1A and Freud-2/CC2D1B [77][78][79]. Unlike REST, which silences neuronal genes mainly in nonneuronal cells, Freud-1 and Freud-2 also repress 5-HT 1A expression in neuronal cells [76].…”
Section: Transcriptional Regulation Of 5-ht 1a Autoreceptors Versus Hmentioning
confidence: 99%